Impacts of ChatGPT on Critical Thinking: Perceptions of Tanzanian Higher Education Students - Valeria Kyumana; George Matto; Jaffar Msafiri Ponera (Journal of Education and Teaching (JET), 2025)
In Tanzania, perceptions toward the adoption of Artificial Intelligence (AI) in education, particularly the use of ChatGPT, are mixed, with debates centered on its effects on critical thinking and traditional learning practices. This study explored students’ perceptions of ChatGPT use in academia and provided future directions. Employing a mixed-methods approach, data were collected from 170 students across two higher education institutions, the Institute of Finance Management (IFM) and Moshi Co-operative University (MoCU). A total of 133 students responded to online questionnaires. Findings revealed that most students (93%) were aware of and used ChatGPT, mainly for study and writing support. Over half (55%) reported a positive influence on critical thinking, while about one-quarter (26.7%) highlighted negative effects, such as overreliance and disruption of traditional learning. Additionally, a large majority (85.2%) viewed ChatGPT as supportive to education, whereas a minority (14.8%) perceived it as a threat, reflecting broader national dilemmas regarding AI adoption. Notably, 43.1% of respondents expressed uncertainty about its misuse, citing the absence of clear policies and guidelines. The study recommends establishing regulatory frameworks for ChatGPT integration to support, rather than replace, critical thinking, human interaction, and creativity, while ensuring ethical practices in academic use.